The art of the con : the most notorious fakes, frauds, and forgeries in the art world - Amore, Anthony M. (Palgrave Macmillan, 2015)
"Art scams are today so numerous that the specter of a lawsuit arising from a mistaken attribution has scared a number of experts away from the business of authentication, and with good reason. Art scams are increasingly convincing and involve incredible sums of money. The cons perpetrated by unscrupulous art dealers and their accomplices are proportionately elaborate. The Art of the Con tells the stories of some of history's most notorious yet untold cons. They involve stolen art hidden for decades; elaborate ruses that involve the Nazis and allegedly plundered art; the theft of a conceptual prototype from a well-known artist by his assistant to be used later to create copies; the use of online and television auction sites to scam buyers out of millions; and other confidence scams incredible not only for their boldness but more so because they actually worked. Using interviews and newly released court documents, The Art of the Con will also take the reader into the investigations that led to the capture of the con men, who oftentimes return back to the world of crime. For some, it's an irresistible urge because their innocent dupes all share something in common: they want to believe"--